2017
DOI: 10.5935/0103-507x.20170025
|View full text |Cite
|
Sign up to set email alerts
|

Factors potentially associated with the decision of admission to the intensive care unit in a middle-income country: a survey of Brazilian physicians

Abstract: Objective To evaluate the factors potentially associated with the decision of admission to the intensive care unit in Brazil.Methods An electronic survey of Brazilian physicians working in intensive care units. Fourteen variables that were potentially associated with the decision of admission to the intensive care unit were rated as important (from 1 to 5) by the respondents and were later grouped as "patient-related," "scarcity-related" and "administrative-related" factors. The workplace and physician charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
(24 reference statements)
1
5
0
1
Order By: Relevance
“…To give precedence to respect of a distributive justice principle, our participants reported to have downgraded principles of autonomy and beneficence (39,40). This is in line with larger quantitative studies which found that patient-related factors were rated higher on their potential to affect decisions than scarcity-related or administrative-related factors (41). Our participants' difficulty in addressing end-of-life issues with patients and their families stresses the importance of providing just-in-time training and simulation sessions for non-ICU clinicians reassigned to work in ICU, to better prepare them for their roles and for addressing sensitive matters (15).…”
Section: Discussionsupporting
confidence: 84%
“…To give precedence to respect of a distributive justice principle, our participants reported to have downgraded principles of autonomy and beneficence (39,40). This is in line with larger quantitative studies which found that patient-related factors were rated higher on their potential to affect decisions than scarcity-related or administrative-related factors (41). Our participants' difficulty in addressing end-of-life issues with patients and their families stresses the importance of providing just-in-time training and simulation sessions for non-ICU clinicians reassigned to work in ICU, to better prepare them for their roles and for addressing sensitive matters (15).…”
Section: Discussionsupporting
confidence: 84%
“…Developed countries like Italy and the United States demonstrate that COVID-19 can overwhelm the healthcare capacities of well-resourced nations very fast (16, 38). Therefore, the SARS-CoV-2 epidemic in middle-income countries, such as Brazil (39), may be devastating. Our findings suggest that strong leadership is needed to coordinate the response efforts against the COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…( 9 ) This situation might partially account for the poorer outcomes usually reported for public ICUs in Brazil. ( 10 ) In addition, operational factors might influence the decision to admit a critically ill patient to the ICU, ( 11 ) which may further complicate the analysis of outcomes.…”
Section: Discussionmentioning
confidence: 99%